2014
DOI: 10.1177/1079063214547581
|View full text |Cite
|
Sign up to set email alerts
|

Examining Specialization Among Sex Offenders Released From Prison

Abstract: A prevailing cultural stereotype about sex offenders is that they tend to specialize in sexual offending. Many recent policy developments-mainly aimed to restrict the liberties of sex offenders-are rooted in this idea. We examined the correctional and arrest records of a sample of 312 sex offenders released on parole in Colorado to determine the prevalence of sexual specialization among these offenders, and to compare the legal and social characteristics of specialists and versatile sex offenders. Overall we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The fact that almost every sex offender knew their victims in one way or another would indicate an ability to interact and create a positive mutual relationship for at least some period of time, and relations need some measure of maturity or at least an understanding of how a social bond is established and maintained (i.e., cooperativeness), why a premise of this kind of crime most probably is a certain level of character maturity. In the ongoing debate about whether sex criminals specialize in sexual offending or if their sex crimes are an expression of their general antisocial behavior leading to a broad array of offenses, our findings also corresponds to some extent with a recent study stating that the rather limited group of individuals specialized in sexual criminality are characterized by a better mental health (i.e., less likely to have received psychiatric or mental health counseling) than what is seen in versatile sex offenders (38). …”
Section: Discussionsupporting
confidence: 88%
“…The fact that almost every sex offender knew their victims in one way or another would indicate an ability to interact and create a positive mutual relationship for at least some period of time, and relations need some measure of maturity or at least an understanding of how a social bond is established and maintained (i.e., cooperativeness), why a premise of this kind of crime most probably is a certain level of character maturity. In the ongoing debate about whether sex criminals specialize in sexual offending or if their sex crimes are an expression of their general antisocial behavior leading to a broad array of offenses, our findings also corresponds to some extent with a recent study stating that the rather limited group of individuals specialized in sexual criminality are characterized by a better mental health (i.e., less likely to have received psychiatric or mental health counseling) than what is seen in versatile sex offenders (38). …”
Section: Discussionsupporting
confidence: 88%
“…These offenders can be identified by the presence of risk markers such as having male victims, having victims both within and outside of their family, and being of younger age. It is also important to note that a significant portion of sexual recidivism may represent crossover offending, that is, offending against a different victim type than earlier sexual offences, although findings have been variable (Cann, Friendship, & Gozna, ; Howard, Barnett, & Mann, ; Kleban, Chesin, Jeglic, & Mercado, ; Lin & Simon, ; Stephens, Seto, Goodwill, & Cantor, ; Levenson, Becker, & Morin, ; Sim & Proeve, ). Offenders with a history of adult victims have been shown to be less consistent in their offending behavior than those with a history of only child victims, with one study showing 37% of those who sexually re‐offend doing so against child victims (Vess & Skelton, ).…”
Section: Discussionmentioning
confidence: 99%
“…The last 20 years have seen an increase in both the number of reported child sexual offences (Australian Institute of Criminology, ) and the number of people in Australia who have been convicted of these offences (Australian Bureau of Statistics [ABS] , ; ABS , ). Not only is the population of known sexual offenders living in the community now considerably larger than it has been in the past (Australian Bureau of Statistics, ), but changes in both the profile of offenders and the types of offence committed may have also occurred (e.g., Lin & Simon, ). For example, the development of the internet has increased access to illicit materials and resulted in more convictions for non‐contact pornography offences that occurred 20 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…They found that more general delinquents, those who committed violence and other types, had earlier starting delinquent careers, evinced more risk factors, and had more criminogenic needs than more specialized violent youth. Indeed, policies who focus on specific types of offenders, such as sexual offenders, are in part predicated on the notion they are disproportionately likely to specialize in sexual aggression (Jennings & Perez, 2018;Lin & Simon, 2016;Miethe, Olson, & Mitchell, 2006;Simon, 2000). 1 In the event that delinquents are versatile and thus evince a general antisocial disposition populated by broad-based risk factors, comprehensive risk assessment and case management tools, such as the level of service/Case Management Inventory (Andrews, Bonta, & Wormith, 2000), and comprehensive correctional interventions, such as multisystemic therapy and functional family therapy (Baglivio, Jackowski, Greenwald, & Wolff, 2014) can be used.…”
mentioning
confidence: 99%
“…They found that more general delinquents, those who committed violence and other types, had earlier starting delinquent careers, evinced more risk factors, and had more criminogenic needs than more specialized violent youth. Indeed, policies who focus on specific types of offenders, such as sexual offenders, are in part predicated on the notion they are disproportionately likely to specialize in sexual aggression (Jennings & Perez, 2018; Lin & Simon, 2016; Miethe, Olson, & Mitchell, 2006; Simon, 2000). 1…”
mentioning
confidence: 99%